The impact of fossil data on annelid phylogeny inferred from discrete morphological characters - Parry, LA; Edgecombe, GD; Eibye-Jacobsen, D; Vinther, J (Royal Society, 2016)
As a result of their plastic body plan, the relationships of the annelid worms and even the taxonomic makeup of the phylum have long been contentious. Morphological cladistic analyses have typically recovered a monophyletic Polychaeta, with the simple-bodied forms assigned to an early-diverging clade or grade. This is in stark contrast to molecular trees, in which polychaetes are paraphyletic and include clitellates, echiurans and sipunculans. Cambrian stem group annelid body fossils are complex-bodied polychaetes that possess well-developed parapodia and paired head appendages (palps), suggesting that the root of annelids is misplaced in morphological trees. We present a reinvestigation of the morphology of key fossil taxa and include them in a comprehensive phylogenetic analysis of annelids. Analyses using probabilistic methods and both equal- and implied-weights parsimony recover paraphyletic polychaetes and support the conclusion that echiurans and clitellates are derived polychaetes. Morphological trees including fossils depict two main clades of crown-group annelids that are similar, but not identical, to Errantia and Sedentaria, the fundamental groupings in transcriptomic analyses. Removing fossils yields trees that are often less resolved and/or root the tree in greater conflict with molecular topologies. While there are many topological similarities between the analyses herein and recent phylogenomic hypotheses, differences include the exclusion of Sipuncula from Annelida and the taxa forming the deepest crown-group divergences.